Orthosteric and benzodiazepine cavities of the α1β2γ2 GABAA receptor: insights from experimentally validated in silico methods - Amundarain, María Julia (2019)
γ-aminobutyric acid-type A (GABA A ) receptors mediate fast synaptic inhibition in the central nervous system of mammals. They are modulated via several sites by numerous compounds, which include GABA, benzodiazepines, ethanol, neurosteroids and anaesthetics among others. Due to their potential as targets of novel drugs, a detailed knowledge of their structure–function relationships is needed. Here, we present the model of the α 1 β 2 γ 2 subtype GABA A receptor in the APO state and in complex with selected ligands, including agonists, antagonists and allosteric modulators. The model is based on the crystallographic structure of the human β 3 homopentamer GABA A receptor. The complexes were refined using atomistic molecular dynamics simulations. This allowed a broad description of the binding modes and the detection of important interactions in agreement with experimental information. From the best of our knowledge, this is the only model of the α 1 β 2 γ 2 GABA A receptor that represents altogether the desensitized state of the channel and comprehensively describes the interactions of ligands of the orthosteric and benzodiazepines binding sites in agreement with the available experimental data. Furthermore, it is able to explain small differences regarding the binding of a variety of chemically divergent ligands. Finally, this new model may pave the way for the design of focused experimental studies that will allow a deeper description of the receptor.